2019
DOI: 10.1515/sspjce-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Study on utilization of zeolite in concrete precast industry

Abstract: Article contains experiment investigating influence of partial cement replacement by zeolite on consistency of fresh concrete, early compressive strength development and temperature development in early stages of curing. Four concrete mixture compositions were tested – containing zeolite in 0%, 5%, 10% and 15% of binder weight. Consistency was tested by flow table test in 5 minutes and 30 minutes after mixing of fresh concrete. Compressive strength and temperature gain were tested after 12, 16, 20 and 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
Order By: Relevance
“… high amount of replacement by zeolite [ 56 , 80 ]; the structure of zeolite (clinoptilolite) crystalline grid-cavities, interconnected by channels, enables water to be stored, leading to a decrease in consistency [ 81 ]; a less amount of water (w/b = 0.3) [ 82 ]. The same is also seen when the results for zeolite and silica fume are compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… high amount of replacement by zeolite [ 56 , 80 ]; the structure of zeolite (clinoptilolite) crystalline grid-cavities, interconnected by channels, enables water to be stored, leading to a decrease in consistency [ 81 ]; a less amount of water (w/b = 0.3) [ 82 ]. The same is also seen when the results for zeolite and silica fume are compared.…”
Section: Resultsmentioning
confidence: 99%
“…Khodabakhshian et al [ 55 ] performed an investigation on the durability performance of structural concrete containing silica fume, concluding on some negative effects of SF on concrete rheology, but showing a positive effect on compressive strength, even in corrosive environments (sodium and magnesium sulphate, sulphuric acid); SF also slightly improved water absorption. In our previous study [ 56 ], we found that increasing the amount of zeolite supplement leads to a decrease in workability, while studying its utilization in the precast industry. Berenguer et al [ 57 ] studied the durability of concrete structures with sugar bagasse ash, while considering it (sample A) as a pozzolanic material to improve the durability properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of ion exchange is facilitated by internal cavities and interconnected channels of molecular size, present in the structure of zeolites [ 31 ]. Natural zeolites occur in hydrated forms, such as clinoptilolite (K 2 Na 2 Ca) 2 [(Al 6 Si 30 )O 72 ]·24H 2 O [ 32 , 33 ]. Their sorption abilities have already been extensively studied by many authors [ 34 ].…”
Section: Introductionmentioning
confidence: 99%